Platelet‐Rich Plasma (PRP) From Older Males With Knee Osteoarthritis Depresses Chondrocyte Metabolism and Upregulates Inflammation - O’Donnell, Christian; Migliore, Eleonora; Grandi, Fiorella Carla; Koltsov, Jayme; Lingampalli, Nithya; Cisar, Cecilia; Indelli, Pier F.; Sebastiano, Vittorio; Robinson, William H.; Bhutani, Nidhi; Chu, Constance R. (Journal of orthopaedic research, 2019)
ABSTRACT There is intense clinical interest in the potential effects of platelet‐rich plasma (PRP) for the treatment of osteoarthritis (OA). This study tested the hypotheses that (i) “lower” levels of the inflammatory mediators (IMs), interleukin‐1β, and tumor necrosis factor α (TNF‐α) and (ii) “higher” levels of the growth factors (GFs), insulin‐like growth factor 1, and transforming growth factor β1 within leukocyte‐poor PRP correlate with more favorable chondrocyte and macrophage responses in vitro. Samples were collected from 10 “healthy” young male (23–33 years old) human subjects (H‐PRP) and nine older (62–85 years old) male patients with severe knee OA (OA‐PRP). The samples were separated into groups of “high” or “low” levels of IM and GF based on multiplex cytokine and enzyme‐linked immunosorbent assay data. Three‐dimensional (3D) alginate bead chondrocyte cultures and monocyte‐derived macrophage cultures were treated with 10% PRP from donors in different groups. Gene expression was analyzed by quantitative polymerase chain reaction. Contrary to our hypotheses, the effect of PRP on chondrocytes and macrophages was mainly influenced by the age and disease status of the PRP donor as opposed to the IM or GF groupings. While H‐PRP showed similar effects on expression of chondrogenic markers (Col2a1 and Sox9) as the negative control group (p > 0.05), OA‐PRP decreased chondrocyte expression of Col2a1 and Sox‐9 messenger RNA by 40% and 30%, respectively (Col2a1, p = 0.015; Sox9, p = 0.037). OA‐PRP also upregulated TNF‐α and matrix metallopeptidase 9 (p < 0.001) gene expression in macrophages while H‐PRP did not. This data suggests that PRP from older individuals with OA contain factors that may suppress chondrocyte matrix synthesis and promote macrophage inflammation in vitro. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:1760–1770, 2019